PEMBERDAYAAN DAN KEGIATAN PETANI MULTIKOMODITI DI PEDESAAN PROPINSI MALUKU: SUATU KAJIAN EKONOMI RUMAHTANGGA - ADOLF B. HEATUBUN; BONAR M. SINAGA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2003)
This study aim to evaluate succession implementing the multicommodity farmers empowering programand to analysis, the impact of external factors change toward farmer’s decision. The farmer’s activity analyzedwith simultaneous econometrics equation approach in the household economic model. Result of the studynamely implementing of the empowering program only success technically, but not success increase thefarmer’s welfare. Utilize and allocation of the labor, agricultural product and farmers disposible income haveincreased caused by increase of the commodity prices, wages and non agricultural income. The farmers shouldincrease the activity motivation and to utilize the effort opportunity available. Program owner need toimprovement the performance in implemented theirs program, in order always orientation to autonomy thefarmers.